Home‐hit improves muscle capillarisation and eNOS/NAD(P)Hoxidase protein ratio in obese individuals with elevated cardiovascular disease risk. (15th July 2019) - Scott, Sam N.; Shepherd, Sam O.; Hopkins, Nicola; Dawson, Ellen A.; Strauss, Juliette A.; Wright, David J.; Cooper, Robert G.; Kumar, Pradesh; Wagenmakers, Anton J. M.; Cocks, Matthew
Abstract : Key points: Obesity and sedentary behaviour are associated with capillary rarefaction and impaired muscle microvascular vasoreactivity, due to reduced nitric oxide bioavailability. Low‐volume high‐intensity interval training (HIT) is a time‐efficient alternative to traditional moderate‐intensity continuous training (MICT), but its effect on the muscle microvasculature has not been studied. The applicability of current laboratory‐ and gym‐based HIT protocols for obese individuals with low fitness and mobility has been disputed by public health experts, who cite the strenuous nature and complex protocols as major barriers. Therefore, we developed a virtually supervised HIT protocol targeting this group that can be performed at home without equipment (Home‐HIT). This study is the first to show that 12 weeks of virtually supervised Home‐HIT in obese individuals with elevated cardiovascular disease risk leads to similar increases in capillarisation and eNOS/NAD(P)Hoxidase protein ratio within the muscle microvascular endothelium as virtually supervised home‐based MICT and laboratory‐based HIT, while reducing many of the major barriers to exercise. Abstract: This study investigated the effect of a novel virtually supervised home‐based high‐intensity interval training (HIT) (Home‐HIT) intervention in obese individuals with elevated cardiovascular disease (CVD) risk on capillarisation and muscle microvascular eNOS/NAD(P)Hoxidase ratio. Thirty‐two adults with elevated CVD risk (age 36 ± 10 years; body mass index 34.3 ± 5 kg m −2 ; V ̇ O 2 peak 24.6 ± 5.7 ml kg min −1 ), completed one of three 12‐week training programmes: Home‐HIT ( n = 9), laboratory‐based supervised HIT (Lab‐HIT; n = 10) or virtually supervised home‐based moderate‐intensity continuous training (Home‐MICT; n = 13). Muscle biopsies were taken before and after training to assess changes in vascular enzymes, capillarisation, mitochondrial density, intramuscular triglyceride content and GLUT4 protein expression using quantitative immunofluorescence microscopy. Training increased V ̇ O 2 peak ( P < 0.001), whole‐body insulin sensitivity ( P = 0.033) and flow‐mediated dilatation ( P < 0.001), while aortic pulse wave velocity decreased ( P < 0.001) in all three groups. Immunofluorescence microscopy revealed comparable increases in total eNOS content in terminal arterioles and capillaries ( P < 0.001) in the three conditions. There was no change in eNOS ser 1177 phosphorylation (arterioles P = 0.802; capillaries P = 0.311), but eNOS ser 1177 /eNOS content ratio decreased significantly following training in arterioles and capillaries ( P < 0.001). Training decreased NOX2 content (arterioles P < 0.001; capillaries P < 0.001), but there was no change in p47 phox content (arterioles P = 0.101; capillaries P = 0.345). All measures of capillarisation increased ( P < 0.05). There were no between‐group differences. Despite having no direct supervision during exercise, virtually supervised Home‐HIT resulted in comparable structural and endothelial enzymatic changes in the skeletal muscle microvessels to the traditional training methods. We provide strong evidence that Home‐HIT is an effective novel strategy to remove barriers to exercise and improve health in an obese population at risk of CVD. Key points: Obesity and sedentary behaviour are associated with capillary rarefaction and impaired muscle microvascular vasoreactivity, due to reduced nitric oxide bioavailability. Low‐volume high‐intensity interval training (HIT) is a time‐efficient alternative to traditional moderate‐intensity continuous training (MICT), but its effect on the muscle microvasculature has not been studied. The applicability of current laboratory‐ and gym‐based HIT protocols for obese individuals with low fitness and mobility has been disputed by public health experts, who cite the strenuous nature and complex protocols as major barriers. Therefore, we developed a virtually supervised HIT protocol targeting this group that can be performed at home without equipment (Home‐HIT). This study is the first to show that 12 weeks of virtually supervised Home‐HIT in obese individuals with elevated cardiovascular disease risk leads to similar increases in capillarisation and eNOS/NAD(P)Hoxidase protein ratio within the muscle microvascular endothelium as virtually supervised home‐based MICT and laboratory‐based HIT, while reducing many of the major barriers to exercise.